‘Let’s get sexting’: risk, power, sex and criminalisation in the moral domain - Murray Lee
This article explores the criminalisation and governance of sexting among young people.While the focus is on Australian jurisdictions, the article places debates and anxieties about sexting and young people in a broader analysis around concerns about new technologies, child sexual abuse, and the risks associated with childhood sexuality. The article argues that these broader social, cultural and moral anxieties have created an environment where rational debate and policy making around teen sexting has been rendered almost impossible. Not only has the voice of young people themselves been silenced in the public, political and media discourse about sexting, but any understanding about the differing behaviours and subsequent harms that constitute teen sexting has been lost. All the while, sexting has been rendered a pleasurable if somewhat risky pastime in an adult cultural context lending weight to the argument that teen sexting is often a subterranean expression of activities that are broadly accepted.The article concludes that the current approaches to regulating teen sexting, along with the emergence of sexting as a legitimate adult activity, may have had the perverse consequence of making teen sexting an even more attractive teenage risk taking activity.Authored by Murray Lee, Thomas Crofts, Michael Salter, Sanja Milivojevic and Alyce McGovern